PENGENDALI ALIRAN AIR BERDASARKAN PEMANTAUAN INTENSITAS UV LAMP STERILIZER PADA PRODUKSI AIR MINUM DALAM KEMASAN BERBASIS IoT - Krisdiyanto; Istiadi; Muhsim, Mohammad (JASEE Journal of Application and Science on Electrical Engineering, 2025)
Bottled drinking water production requires reliable sterilization to ensure microbiological safety after groundwater filtration. Ultraviolet lamps are commonly used as sterilizers; however, decreased light intensity can reduce sterilization effectiveness and affect product quality. This study aims to design and evaluate an Internet of Things-based online monitoring system integrated with Telegram to supervise ultraviolet lamp performance and control product return when the lamp intensity declines. The system was developed using a light-intensity sensor placed at several distances from the ultraviolet lamp, a controller, Telegram notification, and an automatic return valve. Experimental testing was conducted by observing the relationship between sensor distance and received ultraviolet light intensity, followed by regression analysis to determine the warning threshold. The results show that the received light intensity decreases as the sensor moves farther from the ultraviolet lamp, following an exponential trend with a coefficient of determination of 0.8396. When the detected intensity falls below the 75% threshold, the system sends a Telegram warning and activates the return valve to redirect the product to the previous process. Therefore, the proposed system can support real-time monitoring, preventive maintenance, and quality assurance in bottled drinking water production.